Enhanced brain susceptibility to negative stimuli in adolescents: ERP evidences - Yuan, Jiajin; Ju, Enxia; Meng, Xianxin; Chen, Xuhai; Zhu, Siyu; Yang, Jiemin; Li, Hong (Frontiers in Behavioral Neuroscience, 2015)
Background: previous studies investigated neural substrates of emotional face processing in adolescents and its comparison with adults. As emotional faces elicit more of emotional expression recognition rather than direct emotional responding, it remains undetermined how adolescents are different from adults in brain susceptibility to emotionally stressful stimuli. Methods: Event-Related Potentials were recorded for highly negative (HN), moderately negative (MN) and Neutral pictures in 20 adolescents and 20 adults while subjects performed a standard/deviant distinction task by pressing different keys, irrespective of the emotionality of deviant stimuli. Results: Adolescents exhibited more negative amplitudes for HN versus neutral pictures in N1 (100-150ms), P2 (130-190ms), N2 (210-290ms) and P3 (360-440ms) components. In addition, adolescents showed more negative amplitudes for MN compared to neutral pictures in N1, P2 and N2 components. By contrast, adults exhibited significant emotion effects for HN stimuli in N2 and P3 amplitudes but not in N1 and P2 amplitudes, and they did not exhibit a significant emotion effect for MN stimuli at all these components. In the 210-290ms time interval, the emotion effect for HN stimuli was significant across frontal and central regions in adolescents, while this emotion effect was noticeable only in the central region for adults. Conclusions: Adolescents are more emotionally sensitive to negative stimuli compared to adults, regardless of the emotional intensity of the stimuli, possibly due to the immature prefrontal control system over the limbic emotional inputs during adolescence. Keywords: Event-Related Potentials (ERPs); Adolescence; Emotion intensity; Negative pictures; Emotional Susceptibility